REPRESENTASI DISKRIMINASI RASIAL DALAM FILM BUMI MANUSIA: KAJIAN PERSPEKTIF ISLAM TENTANG KEADILAN SOSIAL - Yeni, Desi Fitri; Maijar, Andri (KINEMA: Jurnal Komunikasi dan Penyiaran, 2025)
The research problem in this study is how racial discrimination was carried out by the Dutch colonial government against the indigenous people as depicted in the film Bumi Manusia, and how racial discrimination is viewed from an Islamic perspective regarding social justice, especially as presented in the film Bumi Manusia. The purpose of this study is to examine the forms of racial discrimination in the film Bumi Manusia and how such discrimination is perceived from an Islamic perspective, particularly concerning social justice. This research is qualitative in nature, employing a content analysis approach. The techniques used are divided into three methods: observation, documentation, and literature review. The data that has been reduced is then classified or grouped so that it can be presented and conclusions can be drawn. Based on the research conducted, it can be concluded that out of 230 scenes, 35 scenes contain racial discrimination. Within these 35 scenes, there are 51 segments that depict racial discrimination in the film Bumi Manusia. The forms of racial discrimination presented include social discrimination, systematic discrimination, and institutional discrimination. Discrimination strongly contradicts Islamic values. Islam views all human beings as equal, with no distinction except for a person's piety. This equality is explained in the Qur’an in Surah Al-Hujurat verses 11 and 13, Surah Al-Isra’ verse 70, and Surah Al-Maidah verse 8. Furthermore, Islam also commands its followers to protect their wealth, as stated in the Qur’an in Surah An-Nisa’ verse 29. Positions in Islam are considered a trust (amanah) for a person, as explained in the Qur’an in Surah An-Nisa’ verse 58.